石膏墙板螺杆挤压机溢流加料情况下输送量与螺杆转速的关系研究 - 朱桂华; 李志鹏; 薛洋; 何将三 (Jixie chuandong)
Gesso wallboard screw extrusion machine is the key parts of gesso product line,to achieve enough extrusion mete,overfill adding method is adopted. Because of adopting several screws extrusion,and requiring coming out mete uniformity at landscape orientation and portrait,the connection of rotate speed and the feeding mete should be established. The aim of adjusting the rotate speed and controlling flux accurately is achieved by frequency conversion.